Immediately preoperative use of biological therapy does not influence liver regeneration after large resection--porcine experimental model with monoclonal antibody against epidermal growth factor - Liska, V; Treska, V; Mirka, H; Benes, J; Vycital, O; Bruha, J; Pitule, P; Skalicky, T; Sutnar, A; Chlumska, A; Racek, J; Trefil, L; et al. (In vivo (Athens, Greece), 2012)
BACKGROUND: The aim of this work was to study the influence of isolated biological therapy administered immediately before extended liver resection on liver function and regenerative capacity of future liver remnant (FLR) in a large-animal experiment. MATERIALS AND METHODS: Nineteen piglets were included in this study (10 in the control group and 9 in the experimental group). A port-a-cath was introduced into the superior caval vein. On days 11 and 4 before liver resection, cetuximab was administered via this port at 400 mg/m2 of piglet body surface. Physiological solution was applied to the control group. Resection of the left lateral, left medial and right medial hepatic lobes was followingly performed (reduction of 50-60% of liver parenchyma). Blood samples were collected at different times before the operation and after liver resection. Serum levels of bilirubin, urea, creatinine, alkaline phosphatase, gamma glutamyltransferase, cholinesterase, aspartate aminotransferase, alanine aminotransferase, albumin, C-reactive protein and transforming growth factor-β1 were assessed. The ultrasonographic examinations at different time points were performed pre-operatively and after liver resection in order to assess the liver volume. The biopsies from the liver parenchyma were examined for proliferative activity, binocluated hepatocytes, size of hepatocytes, and the length of the lobuli. The comparison of distribution of the studied parameters between the groups was carried out using the Wilcoxon test. The Spearman rank correlation co-efficient was used because of the non-Gaussian distribution of the parameter values. The whole development of the studied parameters over time was compared between the groups using ANOVA. RESULTS: There were no important complications of administration of biologic therapy during the operation or throughout the peri-operative period. There was no statistically significant difference in the regeneration of FLR nor were any differences in biochemical, immunoanalytical and histological parameters detected. CONCLUSION: The achieved results of comparable liver regeneration in both the experimental and control groups confirms the use of biological treatment with cetuximab in the pre-operative period for minimizing the recovery period.
Keywords: předoperační péče; Preoperative Care; Animals; Liver Regeneration; biologické přípravky; epidermální růstový faktor; Antibodies, Monoclonal; monoklonální protilátky; zvířata; prasata; Swine; Epidermal Growth Factor; Biological Products; regenerace jater